A probabilistic impact-focussed early warning system for flash floods in support of disaster management in South Africa - Rautenbach, C.J. de W. (Cornelis Johannes de Wet) (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2015.